Dançando às avessas: relatos de um processo de criação - Silva, Sandro Souza (2011)
The term body without organs is present in a poem by the french writer, actor and director Antonin Artaud, written in 1947 and titled: To Have Done with the Judgement of God. I aim, in this work, from what we call investigative scenic writing, to problematize this term and its possible relations with the theater and also with some aspects of the Hindu myths. I unite the idea of the body without organs with the body in trance present in the stories of an Indian master named Caitanya Mahaprabhu. These ideas, along with the development of practices that come from some principles of Theatre Anthropology, are incentives for a creation process that highlights the work of preparation and creation of corporeal work of the actor. The relationship between the concepts and the practice raise discussions about where I stand as an actor-researcher in process